Answer: Use a random number generator ranging from 1 to 10 and assign 1 through 4 as the prize and 5 through 10 as no prize.
Step-by-step explanation:
I just did the i-ready lesson, here you go mate! ^-^
Factor out the common term; 3
(3(x + 1))^2 = 36
Use the Multiplication Distributive Property; (xy)^a = x^ay^a
3^2(x + 1)^2 = 36
Simplify 3^2 to 9
9(x + 1)^2 = 36
Divide both sides by 9
(x + 1)^2 = 36/9
Simplify 36/9 to 4
(x + 1)^2 = 4
Take the square root of both sides
x + 1 = √4
Since 2 * 2 = 4, the square root of 2 is 2
x + 1 = 2
Break down the problem into these 2 equations
x + 1 = 2
x + 1 = -2
Solve the first equation; x + 1 = 2
x = 1
Solve the second equation; x + 1 = -2
x = -3
Collect all solutions;
<u>x = 1, -3</u>
Answer:
the first and last ones
Step-by-step explanation:
Answer:
x is 0.
Step-by-step explanation:
Subtract both sides by 3x. Then, you will have 10= x+10. Subtract 10 on both sides to isolate x, then you will have x=0. Therefore, this equation on both sides has a solution of 0. Hope this helps!